Optimization of the drainage system of a single-family residential estate located in the Łódź Voivodeship - Badowska, Ewa (Instal, 2025)
Nowadays, the use of devices for local stormwater retention and infiltration is the most effective method of limiting the negative impact of climate changes and surface sealing, increased in recent decades, on the functioning of urban drainage systems. Moreover, through their aesthetic and utility values, these solutions affect the quality of life in cities. The paper presents used solutions of devices for local infiltration, retention, pretreatment and use of stormwater.  On the basis of the analysis of the multi – variant model of drainage in the area of single – family houses,  the effectiveness of various stormwater management systems was also assessed. The simulation studies were carried out in the EPA SWMM software.
Keywords: rainwater; drainage systems; retention and infiltration; SWMM